An Ultrasensitive Organic Semiconductor NO2 Sensor Based on Crystalline TIPS-Pentacene Films - Wang, Zi (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.